Дослідження еволюції активних ділянок на Сонці - Ковальчук, М.; Гірняк, М.; Лаба, І.; Стоділка, М. (Праці наукового товариства ім. Шевченка, 2011)
The distribution of different types of solar activity is the reflection of its global magnetic field. The generation of the global magnetic field occurs as a result of stochastic movements of solar plasma while the solar magnetic field is an accidental function either of coordinates or of time. This fact grounds the application of stochastic method from the theory of Markov processes to the research of the distribution of active regions on the solar surface and their connection with large scale magnetic field. The analysis of the obtained results (data) enabled us to describe the evolution of an active region that had been explored and become a base for a short term forecast of solar activity.